Nilai Slump, Porositas Dan Kuat Tekan Beton OPC Dan OPC RHA Untuk Aplikasi Di Lingkungan Gambut - Alfadh, Mhd Raja; Kamaldi, Alfian; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The aggressive environment, especially the peat environment contains many chemicals that can unravel the elements in the concrete, causing damage to the concrete. This study examines the strength and physical properties of OPC (Ordinary Portland Cement) concrete and OPC RHA (Rice Husk Ash) concrete exposed in peat environments. RHA as one of pozzolan with high silica is used as a replacement of cement with the substitution of 5% and 10%. This concrete are tested mechanically and physically such as compressive strength and porosity tests after soaking in peat canals for 28 days, in addition to fresh concrete tests such as workability. The concrete strength of the planned concrete is K-250. The peat water used as a test immersion medium has a pH of 3.5-4.5. The results of fresh concrete testing show that the addition of RHA makes the workability decreases. The lowest workability was obtained from a mix containing 10% RHA. The OPC concrete has the highest compressive strength of 20,28 MPa. Porosity of OPC RHA concrete decreased with increase in curing time. The lowest porosity is shown by OPC RHA 10% concrete. Based on the results of the test, it is concluded that the replacement of cement by RHA, has a positive effect on all physical properties of concrete.Keywords: Peat Environtment, OPC, RHA, Compressive strength, Physical Properties